Kinerja Penyuluh Pertanian dalam Melaksanakan Kegiatan Penyuluhan Hortikultura di Kecamatan Wua-Wua Kota Kendari - Wayan Widiana; Dasmin Sidu; Sitti Nur Isnian (Fakultas Pertanian Universitas Halu Oleo, 2021)
This study aims to: (1) determine the performance of agricultural extension workers in carrying out horticultural extension activities, (2) determine the income earned by horticultural farmers. This research was conducted in Wua-Wua District, Kendari City, which was carried out from February to July 2021 with a total of 22 samples determined by proportional random sampling using the Slovin formula. The data in this study were analyzed quantitatively. The data from the research show that (1) the performance of agricultural extension workers in Wua-Wua District, Kendari City still needs to be improved, especially at the stage of implementing agricultural extension (2) the income earned by horticultural farmers in Wua-Wua District, Kendari City, which is IDR 2.598.000/ planting season, for kale, mustard greens, and spinach, the income is below the average salary of Kendari City's UMR.